Risk Management's Role in Coffee Shop Business Continuity: The Case of Brewandy - Dewita, Kadek Putri; Rahayu, Ni Putu Widhia (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to explore and improve the risk management practices of Brewandy Coffee, a micro, small, and medium enterprise (MSME) in the café sector, by evaluating existing strategies and suggesting enhancements. Methodology: The research uses a descriptive qualitative methodology to examine risks through the ISO 31000 framework and Risk and Self-Control Assessment (RSCA). Data were collected through in-depth interviews with stakeholders, including consumers, owners, and employees, to analyze and assess risks based on their frequency and impact. Results: The results show that Brewandy Coffee’s risk management strategies, including real-time monitoring, employee training, supply chain diversification, and enhanced data security, align with industry standards, effectively mitigating operational risks. Findings: The study highlights that adapting industrial-scale risk management practices to MSMEs is essential for business resilience and operational efficiency in resource-constrained environments. Novelty: The novelty of this study lies in integrating multiple perspectives—stakeholders’ views and risk management frameworks—into MSME risk practices, offering a holistic approach to improving risk management strategies. Originality: This paper is original in addressing the gap in MSME literature by applying advanced risk management practices in small enterprises, particularly in the café sector. Conclusions: The study concludes that risk management is critical for long-term sustainability and provides practical insights for MSMEs to enhance their risk mitigation strategies. Type of Paper: Descriptive qualitative research paper.